POLYOSTOTIC FIBROUS DYSPLASIA - Bundovska, Smiljana; Antuleska, Gordana; Petrovski, Aleksandar; Peneva, Elena (Journal of Morphological Sciences, 2022)
Fibrous dysplasia is a benign skeletal disorder in which the normal bone tissue is replaced by immature fibrous tissue. Polyostotic means that abnormal areas may occur in many bones; often they are confined to one side of the body. Replacement of bone by fibrous tissue may lead to pathologic fractures, uneven growth, and deformity. CT and MRI findings in combination with histopathological results are crucial for the diagnosis of this condition. We present a specific case of a patient with polyostotic fibrous dysplasia and the imaging findings that lead to the final diagnosis.              Keywords : fibrous dysplasia, polyostotic, CT, MRI.